The novel long noncoding RNA AU021063, induced by IL-6/Arid5a signaling, exacerbates breast cancer invasion and metastasis by stabilizing Trib3 and activating the Mek/Erk pathway. (1st November 2021) - Nyati, Kishan Kumar; Hashimoto, Shigeru; Singh, Shailendra Kumar; Tekguc, Murat; Metwally, Hozaifa; Liu, Yu-Chen; Okuzaki, Daisuke; Gemechu, Yohannes; Kang, Sujin; Kishimoto, Tadamitsu
Abstract: Interleukin (IL-6) is a pleotropic cytokine with both tumor-promoting and -inhibitory effects on breast cancer growth. However, the mechanisms governing the outcome of IL-6 on cancer progression remain to be clarified. Our study unraveled a novel long noncoding RNA (lncRNA) AU021063 downstream of IL-6 signaling. We found that IL-6 induced the expression of AU021063 predominantly in breast cancer compared to other cancer types. Mechanistically, IL-6 induced AT-rich interactive domain 5a (Arid5a) expression, which promotes the transcription of AU021063. In turn, AU021063 promotes breast cancer metastasis through stabilizing tribbles homolog 3 (Trib3) and activating Mek/Erk signaling pathway. Genetic ablation of either Arid5a, AU021063 or Trib3 abolished breast cancer metastasis in vitro and in vivo . Overall, our study highlights the importance of IL-6-Arid5a-AU021063 axis in regulating breast cancer invasiveness and metastasis, which may provide potential novel therapeutics for breast cancer. Highlights: The IL-6/Arid5a axis upregulates AU021063 expression in breast cancer cells. AU021063 stabilizes the Trib3 and activates Mek/Erk pathway in breast cancer cells. AU021063 and Trib3 promote invasion and metastasis in vitro and in vivo . Trib3 is required for AU021063-mediated invasion and metastasis of breast cancer cells.